INFECTIOUS DISEASES AND THE ENVIRONMENT: BASELINE INFORMATION FROM STAKEHOLDERS IN CROSS RIVER STATE, NIGERIA - Osuchukwu, N. C; Agba, A. M. Ogaboh; Emeh, J. U. (International Journal of Research -GRANTHAALAYAH, 2017)
The prevalence of environment related infectious diseases in sub-Saharan Africa despite concerted efforts to prevent and reduce its spread is worrisome. African remains the continent that pays the greatest prince, bearing roughly two-third-of mortality burden from infectious diseases. The concern of this study therefore is to examine reactions from stakeholders in Cross River State, Nigeria on the state of the environment, education/curriculum and the spread of infectious diseases. Seventy (70) stakeholders were purposively selected for the study. Qualitative technique that is Focus Group Discussion (FGD) was used to generate data from selected participants. Five FGDs comprising of fourteen (14) persons each was used for the study. Group discussions were based on themes/questions that reflect on the environment, infectious diseases and the curriculum in primary and secondary schools. Baseline information from participants revealed that curriculum contents at primary and secondary education levels do not adequately address issues of infectious diseases and the environment. We recommended among others the infusion of vital aspects of infectious diseases (ID) and environmental education (EE) in the curriculum contents of primary and secondary schools in Nigeria.